2019
DOI: 10.1111/asj.13309
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of varying fermentation conditions with ensiling period and inoculum on photosynthetic pigments and phytol content in Italian ryegrass (Lolium multiflorum Lam.) silage

Abstract: Photosynthetic pigments in forage such as chlorophyll and carotenoids have vital roles in animal health and affect the quality of dairy products (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…And, the pheophytin, pheophorbide, chlorophyllide and phytol are also produced during the decomposition of chlorophyll. Previously, it has been found that during silage, about 75% and 25% of chlorophyll and β-carotene in IR were decomposed and the changes of lutein were slight, also, the phytol was preserved in an esterified form and not affected by silage quality (Lv et al, 2020).…”
Section: Effect Of Drying On Nutrients and Photosynthetic Pigments In Herbagementioning
confidence: 96%
See 1 more Smart Citation
“…And, the pheophytin, pheophorbide, chlorophyllide and phytol are also produced during the decomposition of chlorophyll. Previously, it has been found that during silage, about 75% and 25% of chlorophyll and β-carotene in IR were decomposed and the changes of lutein were slight, also, the phytol was preserved in an esterified form and not affected by silage quality (Lv et al, 2020).…”
Section: Effect Of Drying On Nutrients and Photosynthetic Pigments In Herbagementioning
confidence: 96%
“…Nitrogen (N) fertilizers can increase the content of crude protein (CP) and carotenoids (β-carotene) in forages (Kopsell et al, 2007;Lv et al, 2020). Because β-carotene is easily oxidized once plants are harvested, β-carotene content in stored forages is lower than that in fresh ones (Bruhn & Oliver, 1978;Kalač & McDonald, 1981;Park et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…These include the β-carotene isomers, 13-cis and all-trans, in addition to 5 of the xanthophyll class, violaxanthin, antheraxanthin, lutein, zeaxanthin and epilutein, each representing 4%, 11%, 14%, 3%, 49%, 10% and 9% of total carotenoid content, respectively [61]. [79,80]. The ensiling process reduced β-carotene in Virginia Fanpetals by 56% [81].…”
Section: Dietary Sources For Bovine Carotenoid Consumptionmentioning
confidence: 99%
“…Moreover, the forage processing and modulation method also affects the pigment content; Lv et al (2021) reported that drying can obviously reduce the content of chlorophyll and phytol in the harvest grass. On the contrary, ensiling could preserve the phytol in temperate grasses Italian ryegrass well (Lv et al, 2017;Lv et al, 2020). Phytol is produced by chlorophyll degradation in acidic environments, and the acidity of silage may be the key factor of phytol conversion.…”
Section: Introductionmentioning
confidence: 99%